Analysis of genetic diversity and genetic structure of indigenous chicken populations in Guizhou province based on genome-wide single nucleotide polymorphism markers - Sheng Wu; Zhiwen Chen; Xiaohong Zhou; Juanhong Lu; Yingping Tian; Yaozhou Jiang; Qinsong Liu; Zhong Wang; Hui Li; Lujiang Qu; Fuping Zhang (Poultry Science)
ABSTRACT: Guizhou province in China is rich in indigenous chicken breeds, playing an essential role in the genetic improvement of modern chickens. Genetic diversity has decreased in recent decades due to accelerated breeding processes and changing conservation priorities. To determine the genetic diversity and population structure of Guizhou indigenous chicken breeds, we used 55K genotyping arrays to conduct population genetic analysis on 233 individuals from 8 Guizhou indigenous breeds and 263 individuals from 9 Guizhou indigenous chicken populations. We evaluated the genetic diversity parameter (heterozygosity, proportion of polymorphic markers, and nucleotide diversity), linkage disequilibrium (LD), population structure, and genetic differentiation (FST and genetics distance). Genetic diversity results indicated that the genetic diversity of chicken breeds in Guizhou province is relatively affluent. Among Guizhou breeds, Baiyi black-bone and Guizhou yellow chicken displayed the lowest genetic diversity, as the 2 breeds exhibit lower PN and heterozygosity, the extent of linkage disequilibrium is higher. According to the LD pattern, Guizhou indigenous breeds can be divided into 3 categories. Population structure analysis showed a certain degree of genetic differentiation among local chickens in Guizhou. We argue that Chishui black-bone and Puan black-bone chickens are 2 different geographical regional groups of the same breed. In principal component analysis, individuals from the 2 groups clustered together, and the phylogenetic tree results showed that the 2 groups clustered together to form a branch independent of other breeds, and they displayed an identical pattern of ancestral lineage composition. The research results will provide a reference for protecting local chicken genetic resources in Guizhou Province and promote the protection and utilization of genetic resources.